High voltage discharge profile on soil breakdown using impulse discharge - Fajingbesi, Fawwaz Eniola; Midi, Nur Shahida; Elsheikh, Elsheikh Mohamed Ahmed; Yusoff, Siti Hajar (IOP Publishing, 2017)
Grounding terminals are mandatory in electrical appliance design as they provide safety route during overvoltage faults. The soil (earth) been the universal ground is assumed to be at zero electric potential. However, due to properties like moisture, pH and available nutrients; the electric potential may fluctuate between positive and negative values that could be harmful for internally connected circuits on the grounding terminal. Fluctuations in soil properties may also lead to current crowding effect similar to those seen at the emitters of semiconductor transistors. In this work, soil samples are subjected to high impulse voltage discharge and the breakdown characteristics was profiled. The results from profiling discharge characteristics of soil in this work will contribute to the optimization of grounding protection system design in terms of electrode placement. This would also contribute to avoiding grounding electrode current crowding, ground potential rise fault and electromagnetic coupling faults.